Ten Years of the Global Reform of Financial Regulation: What is ahead? - L. S. Khudyakova (Vestnik MGIMO-Universiteta)
Global financial crisis of 2008–2009 demonstrated the need for reforms in the system of financial regulation. An institutional mechanism was created under the auspices of the G20 with the purpose to implement a global reform. In the article results of the postcrisis global financial reform are analysed in contingent with review of the evolution of institutional mechanism, which specifics often determined success or its absence in particular directions of the reform. The author selects and reviews three main periods of development of the global financial regulation’s institutional mechanism. In the initial period – the first years after the crisis works were progressing in two directions simultaneously: a) co-ordination of activities of national financial regulatory bodies in coping with the crisis processes and neutralization of its consequences; b) development and reconciliation of major global standards of financial regulation. We can consider that period as successful because crisis processes were overcame in relatively short time, trade and currency wars were also avoided and at the same time international regulatory standards were widely agreed.The second period according to the author’s classification (approx. 2012–2015) – transmission to the implementation of agreed international standards at the national and supranational (EC) levels. That time a range of difficulties and contradictions between leading countries revealed. First of all these problems related to the spheres where the regulations of transnational activities of financial institutions had to be agreed. As the author shows exactly in that time a problem of the so-called asymmetrical sovereignty in the financial policy aggravated.The third period is continuing in the present time. During this period, from the one side, the global financial regulation expands its coverage according to emergence of new challenges, but from the other side the interest to the reform is being loosing and the trend to increase of the independence of the national financial regulators is expanding. So the threat to fragmentation of the international financial markets and revision of already agreed regulatory standards became not illusive.Special attention in the article was paid to analysis of the problem of regulating the shadow banking or non-bank financial intermediation (NBFI), which are till now largely outside of the regulatory mandate of the governance bodies. Rapid growth of transactions by the latter, according to the author’s opinion, is a threat to the global financial stability especially taking into account such factors as its close interconnectedness with traditional financial institutions (banks), exposure to the bank-like risks, the wide implementation of financial innovations for making new unregulated products.Investigating new challenges beyond the perimeter of the post-crisis reform the author came to the conclusion that implementation of financial technologies as well as the necessity to take into account ecological and social factors require serious transformation of the global financial system as well as it’s regulation. Taking into account the global nature of new challenges the need for international co-operation of financial regulatory bodies will be continued.